Oxidative and selective C-C cleavage of glycerol to glycolaldehyde with atom-like Cu on Cu-TiO2: photocatalytic water reduction with concurrent glycerol oxidation in sunlight - Bajpai, Himanshu; Nivedhitha, Thazhath R.; Dais, Elsa; Kanungo, Subhashree S.; Gopinath, Chinnakonda S. (Journal of Catalysis, 2024)
Concurrent consumption of electrons and holes for the conversion of a biomass component to value added products represents a highly efficient and sustainable approach towards utilizing renewable energy, but difficult to achieve. The integration of hydrogen production with glycerol oxidation presents a novel and sustainable approach towards achieving a circular economy. In the current study, integration of atom-like Cu-clusters onto TiO2 substrate has been achieved using a facile photo-deposition technique (TC-PDO). Also, novel synthetic approaches have been employed to augment the surface coverage of Cu on TiO2 with atom-like clusters of Cu, either by borohydride treatment on TiO2 followed by Cu-deposition (TC-200) or oxygen-vacancy creation by UV illumination followed by Cu-deposition (TC-PDO). Increased dispersion and enhanced electronic integration of Cu with TiO2 lead to a corresponding increase in the efficiency of photocatalytic hydrogen evolution (13.8 mmol/h.g for TC-PDO at pH 9). Several atom-like Cu integrated with each TiO2 particle acts as photocatalytic reactor, and the same enhances electron-hole separation as well as activity. Sustainable aspect was also studied for TC-PDO up to 25 h at pH 9. Concurrently, glycerol oxidation displays the highest selectivity to C2 product (glycolaldehyde with 70 %) with a C-C cleavage. The investigation of this process holds significant potential for the extensive and simultaneous exploitation of electrons and holes in order to achieve water splitting and glycerol oxidation towards selective value-added products formation.
Keywords: C -C Cleavage; Glycerol; nanotechnology; Photo -deposition; solar energy conversion